2019
DOI: 10.1055/a-1010-6449
|View full text |Cite
|
Sign up to set email alerts
|

Could Vitamin D be Associated with Proliferative Diabetic Retinopathy? Evidence from Pooling Studies

Abstract: Contrasting data about the association between proliferative diabetic retinopathy (PDR) and vitamin D status remain unknown. First, a hospital-based cross-sectional study consisting of 889 diabetic retinopathy (DR) and non-DR (NDR) patients was admitted. Further the accumulated evidence was performed to explore the association and dose-response relationship. Our study indicated that the odd ratio for PDR in vitamin D deficiency (VDD) individuals was significantly increased (1.60, 95% CI 1.06–2.42), compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition, VDD was found to be associated with a higher prevalence of complications in patients with diabetes, such as neuropathy, nephropathy, and retinopathy [ 43 , 50 ]. Some studies found patients with DM and VDD had an increased risk of developing DR [ 47 , 51 , 52 , 53 , 54 ]. Another study also found higher odds of developing DR in patients with type 1 diabetes and VDD [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, VDD was found to be associated with a higher prevalence of complications in patients with diabetes, such as neuropathy, nephropathy, and retinopathy [ 43 , 50 ]. Some studies found patients with DM and VDD had an increased risk of developing DR [ 47 , 51 , 52 , 53 , 54 ]. Another study also found higher odds of developing DR in patients with type 1 diabetes and VDD [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As of 2010, this eye disorder affected over 100 million patients worldwide, and this number is expected to almost double by the year 2030 [ 45 , 46 ]. Studies indicate that that patients with DR had lower serum levels of vitamin D compared with those without [ 47 ] and that vitamin D (25-hydroxyvitamin D) deficiency is significantly associated with an almost twofold greater risk of DR [ 48 , 49 , 50 , 51 , 52 , 53 ], especially the proliferative form [ 54 , 55 ]. This dependence has been observed for patients with type 1 and type 2 diabetes mellitus [ 56 , 57 , 58 ].…”
Section: Vitamin D Vdr and Calcitriol Analogues In Ocular Diseasesmentioning
confidence: 99%
“…Vitamin D deficiency (VD) is a global problem, some studies reporting its presence in 82.5% of subjects, with an increased frequency even in countries with year-round sunlight. VD deficiency is given by serum levels of 25 (OH) D below 20 ng/ ml [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%